A Deeply Interpreting of Student Growth Percentile Model: Promoting the Application of Value-added Evaluation - Fan, Yaqin (South Sulawesi Education Development, 2026)
The increasing number of independent variables and dependent variables, the correction of covariates and the cross-influence between variables all promote the evolution and development of value-added evaluation model. As one of the value-added evaluation models, the student growth percentile model is one of the most popular value-added evaluation models with its easy to understand core concept and relatively simple operation process. However, for primary and secondary school teachers, the model still has certain difficulties in practical application, and the technical requirements are beyond the public level. In order to promote the application and further development of the percentile model of student growth, this paper discusses it from the basic theory, application operation, limitation and development, so as to promote the theoretical understanding of the model and the operation process to be more specific.